2020
DOI: 10.1155/2020/7931950
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathogenic Characteristics of Lower Respiratory Tract Infection Treated at the Vietnam National Children’s Hospital

Abstract: Lower respiratory tract infections are commonly caused by viruses and cause significant morbidity and mortality among children. Early identification of the pathological agent causing these infections is essential to avoid unnecessary antibiotic use and improve patient management. Multiplex PCR techniques were recently developed to detect multiple viral pathogens using a single PCR reaction. In this study, we identify viral pathogens in children with respiratory infections. We collected 194 nasopharyngeal aspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…We observed a high rate of LRTI and influenza in hospitalised children. Previous studies in Vietnam showed that respiratory syncytial virus, enterovirus/rhinovirus, parainfluenza virus and adenovirus were frequently associated with LRTI [ 18 23 ]. Bacteria classically described to cause community-acquired pneumonia in Vietnamese children include Streptococcus pneumoniae , Hib and Staphylococcus aureus [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a high rate of LRTI and influenza in hospitalised children. Previous studies in Vietnam showed that respiratory syncytial virus, enterovirus/rhinovirus, parainfluenza virus and adenovirus were frequently associated with LRTI [ 18 23 ]. Bacteria classically described to cause community-acquired pneumonia in Vietnamese children include Streptococcus pneumoniae , Hib and Staphylococcus aureus [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on 722 hospitalised Vietnamese children [ 25 ], showed that atypical pathogens were identified in 29.8% of cases, mainly Mycoplasma pneumoniae (26.3%). Viral and virus-bacteria co-­infections were frequently detected in children with LRTI [ 18 21 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute lower respiratory tract infections (ALRIs) are the substantial cause of morbidity and mortality in children, especially in developing countries. [ 1 2 ] Pneumonia and bronchiolitis are most common among children. [ 3 ] Worldwide, around 18% of annual deaths in children below 5 years of age occur due to pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…The most important agent of ARIs which can cause a wide range of infections in the upper and lower respiratory tract are viruses (Leung et al 2020;Bhuyan et al 2017;Botti et al 2018). Here, more well-known respiratory viruses are influenza, parainfluenza, rhinovirus (RV), coronavirus (CoV), adenovirus, and respiratory syncytial virus (RSV) (Nichols et al 2008;Modena et al 2011;Pham et al 2020). CoVs are a large family of viruses ranging from the common cold virus to the causes of more serious diseases such as severe acute respiratory syndrome (SARS), middle east respiratory syndrome (MERS), and CoV disease 2019 Paules et al 2020).…”
mentioning
confidence: 99%